The Social and Philosophical Values of the Positivization of Islamic and Customary Law in Indonesia - Nur Alifah; Roibin (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
The complexity of the positivization of Islamic and customary law in Indonesia’s national legal system is not merely normative. However, it is also significantly influenced by social, political, and ideological factors. Although Islamic and customary law have considerable potential to contribute to the development of the national legal system, their integration often fluctuates depending on the prevailing political-legal configuration. This inconsistency underscores the importance of a socio-philosophical approach to understanding how moral values, cultural norms, and socio-political interests shape a national legal system that is both just and contextually relevant. This article explores the socio-philosophical dynamics of positivizing Islamic and customary law within Indonesia's national legal framework. Employing a qualitative approach and literature-based research method, this study focuses on three main issues: first, the position of Islamic and customary law in the development of national law; second, the process of their positivization; and third, a socio-philosophical analysis of that process. The socio-philosophical approach examines how moral values, cultural traditions, and socio-political interests influence legal positivization. The study finds that Islamic and customary laws interact constructively in developing the national legal system. However, the positivization process remains fluid and contingent on the prevailing political and legal climate. Furthermore, the socio-philosophical perspective reveals that incorporating Islamic and customary law reflects the nation's social structure, divine values and cultural identity. This approach is essential for understanding legal development holistically, ensuring that national law is not only formally just but also socially and culturally relevant.